Peran Pusat Pendidikan dalam Sosiologi Pendidikan Islam : Menjawab Tantangan Gender dan Membangun Karakter - Okta Fasya Fitri Romadhona; Siti Ratna Oktafiani; Umi Anjaliya Salma; Mu'alimin Mu'alimin (Moral : Jurnal kajian Pendidikan Islam, 2024)
Islamic religious education plays a crucial role in shaping individual character and fostering a harmonious society. This article examines the role of Islamic religious education within families and communities through a literature study approach, analyzing five relevant articles. The findings indicate that religious education in families, based on Islamic values, serves as the primary foundation for shaping good individual behavior and noble character. Moreover, Islamic religious education contributes to strengthening a more inclusive and harmonious social structure. However, challenges related to gender roles in religious education and limitations in its implementation remain significant issues. The article also suggests that future research consider the role of government policies and technological advancements in enhancing the application of Islamic religious education. Thus, this study contributes to the development of understanding regarding the importance of Islamic religious education in family and community contexts.